A 21st Century Paradigm for Evaluating the Health Hazards of Nanoscale Materials? - Walker, Nigel J. (Oxford University Press, 2009)
Over the past 5 years we have seen an increase in the attention focused on the assessment of the potential health risk posed by nanoscale materials. The diversity of these materials with respect to size, composition, and surface properties, and the rapid pace of their development and commercialization, poses significant challenges to traditional toxicity testing paradigms. At the same time the potential use of new high throughput “predictive “toxicity” strategies, such as that envisioned in the recent NRC report “Toxicity Testing in the 21st Century,” have emerged as possible solutions to deal with the issue of how to assess the safety of the thousands of chemicals to which humans are potentially exposed. In this forum article we discuss how in some respects, the emergence of diverse engineered nanomaterials offers a tailor-made test case for the application of a new paradigm for assessing human heath risks. However, although this approach may have merit in the study of some specific nanomaterials, this approach does not consider the complexity involved in utilizing in vitro cell culture toxicology methods to evaluate the potential hazard of the wide array of current and future engineered nanomaterials.